Preclinical safety evaluation of intradermal SARS-CoV-2 inactivated vaccine (Vero cells) administration in macaques. Issue 17 (24th April 2023) - Yang, Jinling; Huo, Xinqian; Jiang, Qinfang; Liao, Yun; Zhang, Caixing; Yu, Li; Wang, Qiyan; Niu, Tingting; Li, Cong; Pi, Na; Li, Yun; Zhao, Heng; et al.
Highlights: Intradermal administration of a SARS-CoV-2 inactivated vaccine induced strong humoral and cellular immunity in rhesus macaques; The SARS-CoV-2 inactivated vaccine showed good safety and immunogenicity; There were no adverse reactions related to the SARS-CoV-2 inactivated vaccine. Abstract: Coronavirus disease 2019 (COVID-19) is an acute and highly pathogenic infectious disease in humans caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Six months after immunization with the SARS-CoV-2 vaccine, however, antibodies are almost depleted. Intradermal immunization could be a new way to solve the problem of nondurable antibody responses against SARS-CoV-2 or the poor immune protection against variant strains. We evaluated the preclinical safety of a SARS-CoV-2 vaccine for intradermal immunization in rhesus monkeys. The results showed that there were no obvious abnormalities in the general clinical condition, food intake, body weight or ophthalmologic examination except for a reaction at the local vaccination site. In the hematology examination, bone marrow imaging, serum biochemistry, and routine urine testing, the related indexes of each group fluctuated to different degrees after administration, but there was no dose–response or time-response correlation. The neutralization antibody and ELISpot results also showed that strong humoral and cellular immunity could be induced after vaccination, and the levels of neutralizing antibodies increased with certain dose- and time-response trends. The results of a repeated-administration toxicity test in rhesus monkeys intradermally inoculated with a SARS-CoV-2 inactivated vaccine showed good safety and immunogenicity.